TO WHAT EXTENT CAN ELECTRONIC PARLIAMENT BE APPLIED IN JORDAN - Soultanian, Victor Setrag George (European Scientific Journal, ESJ, 2013)
The paper aimed to investigate the extent of application use of electronic Parliament techniques in Jordan and identifying the most important requirements and difficulties that face the application of this technology. The paper concluded that the infrastructure is available for the application of this technique and that the majority of parliament are able to deal with this technique efficiently, but there are some difficulties that hinder such represented by acceptance of other's opinion and their willingness to adapt with this technique.